Healing the 'split': trauma as a dynamic in psychosis. (1st July 2021) - Franco, Lucia; Nicholls, Lindsey
Abstract : In this article, the first author uses an autobiographical account of a trauma she experienced and shows how, in her understanding, this led to her developing what was diagnosed as paranoid schizophrenia. The trauma forced her to accept a distortion of her understanding of reality, which, she explains, caused a split in her ego between the inner truth of the event and the imposed distortion. She considers Freud's theory of how trauma develops and looks at how it applies to her case. Using Winnicott's theory of there being a 'false self' in psychosis, she shows how a false self was formed out of the distortion. Bion's understanding of the development of thought applied to trauma is used to give insight into how the mind finds it difficult to process thought when a trauma occurs and, using Brown's understanding, she indicates how this is similar to what happens in psychosis. She utilizes Winnicott's explanation of there being a trauma not lived through, as if not experienced, being present in psychosis and how the need to experience, 'remember', this trauma is for healing to take place. In conclusion, she argues how the reaching and establishing of the inner truth is what is needed for recovery to happen and for the split in the ego to heal.